Magnetoledtherapy in the treatment of wounds after surgical procedures of the knee joint - Pasek, Jarosław (Dove Medical Press, 2014)
The intense development of methods of physical medicine has been noted recently. The new methods are treatment methods, which in many cases allow a reduction of treatment time and positively influence the quality of life of patients undergoing treatment. This applies to illnesses and injuries of the locomotor system and diseases affecting soft tissues, as well as chronic wounds. This article discusses the positive results of the treatment of a 63-year-old woman with a persisting chronic wound of her right lower extremity after knee joint endoprosthesis surgery. The physical medicine method applied, in the form of magnetoledtherapy, contributed to complete wound healing and alleviation of pain suffered, as well as improvement of the quality of life of the treated patient.